Maternal and Clinical Outcomes of Placenta Accreta Spectrum: Insights from a Retrospective Study in Bahrain - Kareeza Selby Chacko; Reem Satam AlSubeaei; Soumya Sunil Nair; Nusrat Khalil Kazi; Rafiea Jeddy (Life, 2025)
Placenta accreta spectrum (PAS) refers to a group of abnormal placental attachments in which the placenta adheres too deeply to the uterine wall, with varying degrees of invasion classified as accreta, increta, or percreta. Increased rates of uterine surgeries, advanced maternal age, and cesarean deliveries have all contributed to an increase in the incidence of PAS. Complications associated with PAS can lead to severe intrapartum or postpartum hemorrhage, hysterectomy, and significant maternal morbidity, making early diagnosis and management crucial for improving outcomes. Understanding the epidemiology and risk factors of PAS is crucial for developing early detection protocols and preventive strategies. Localized data, particularly from Bahrain, can inform targeted care approaches and optimize resource allocation, ultimately leading to improved clinical guidelines, enhanced patient education, and better healthcare outcomes for affected women. There are growing concerns about the impact of PAS on maternal health and healthcare resources in Bahrain, similar to trends observed in other regions. To improve patient education and management strategies, it is essential to comprehend the regional patterns, characteristics, and outcomes associated with PAS. However, the absence of comprehensive data specific to Bahrain hinders effective clinical decision-making and policy development. Addressing this gap is imperative for advancing maternal healthcare in the region.